Christmas cake murder [compact disc, unabridged] - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery., 2018)
Juggling the responsibilities of opening her shop with the demands of Christmas, Hannah Swensen is surprised by the writing talents of an elderly local whose murder story chillingly comes true.